Psychosocial factors at work, long work hours, and obesity: a systematic review - Svetlana Solovieva; Tea Lallukka; Marianna Virtanen; Eira Viikari-Juntura (Nordic Association of Occupational Safety and Health (NOROSH), 2013)
OBJECTIVES: Associations between psychosocial work environment and excess weight have not been systematically addressed. The aim of this systematic review was to summarize the published evidence for the associations of psychosocial factors at work and long work hours with weight-related outcomes . Methods We conducted a search of Medline and Embase for all original articles published up to September 2012 using predefined keywords. After excluding studies with a definite selection bias, we included 39 articles. RESULTS: About 60% of the studies reported at least one positive association between psychosocial factors at work and a weight-related outcome. However, 76% of the tested associations were found to be non-significant. Furthermore, the associations were rather weak. Studies of higher quality tended to observe associations more often than those of lower quality. Positive associations were found more frequently (i) among women versus men, (ii) in cross-sectional versus longitudinal studies, and (iii) for overweight or obesity versus other outcomes. About 70% of the studies reported positive associations between long work hours and weight-related outcomes. All four studies that evaluated the association between working overtime and weight gain (three longitudinal and one cross-sectional), showed a positive association among men and two of them also observed associations among women. CONCLUSIONS: We found evidence for weak associations between psychosocial factors at work and excess weight. Associations were observed between long work hours, working overtime, and weight gain, especially among men. More cohort studies among non-obese baseline participants using appropriate analytical methods based on an elaborated hypothetical model are needed.